Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.1016/j.pep.2008.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Purification and enzymological characterization of murine neurotrypsin

Abstract: An increasing number of studies indicate that serine proteases play an important role in structural plasticity associated with learning and memory formation. Neurotrypsin is a multidomain serine protease located at the presynaptic terminal of neurons. It is thought to be crucial for cognitive brain functions. A deletion in the neurotrypsin gene causes severe mental retardation in humans. For a biochemical characterization, we produced murine neurotrypsin recombinantly in a eukaryotic expression system using my… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(35 citation statements)
references
References 13 publications
2
33
0
Order By: Relevance
“…S9, none of these proteins was cleaved by neurotrypsin. These results corroborated previous indications of a highly selective proteolytic activity of neurotrypsin versus agrin (Reif et al, 2007;Reif et al, 2008).…”
Section: Cleavage-resistant Agrin Rescues the Neurotrypsinoverexpresssupporting
confidence: 91%
See 2 more Smart Citations
“…S9, none of these proteins was cleaved by neurotrypsin. These results corroborated previous indications of a highly selective proteolytic activity of neurotrypsin versus agrin (Reif et al, 2007;Reif et al, 2008).…”
Section: Cleavage-resistant Agrin Rescues the Neurotrypsinoverexpresssupporting
confidence: 91%
“…5A). Detailed characterizations of the individual cleavage sites had previously demonstrated that substitution of the basic P1 amino acid by alanine prevented cleavage by neurotrypsin at each site (Reif et al, 2007;Reif et al, 2008). Coexpression tests in HeLa cells confirmed the effect of these mutations by showing the resistance of double-mutated full-length agrin against proteolytic cleavage by neurotrypsin (supplementary material Fig.…”
Section: Cleavage-resistant Agrin Rescues the Neurotrypsinoverexpressmentioning
confidence: 84%
See 1 more Smart Citation
“…The protein starts with L1519 (A2ASQ1 (AGRIN_MOUSE), UniProtKB/Swiss-Prot) and ends with the natural C-terminus of agrin. The fragment contains the z-8 amino acid insert and in addition the lysine to alanine mutation which renders the protein protected against site specific neurotrypsin cleavage at the β-cleavage site [36]. NT-1654 was transiently expressed in CHO-S cells in suspension culture (Evitria, Switzerland) to a level of up to 900 mg/L.…”
Section: Methodsmentioning
confidence: 99%
“…Neurotrypsin cleaves agrin at two homologous conserved sites (α-and β-site), resulting in an N-terminal part, a middle 90-kDa fragment (agrin-90) and a C-terminal 22-kDa fragment (agrin-22). However, short peptides only consisting of the amino acid sequence of the αor β-site are not cleaved by neurotrypsin, indicating that the specificity of neurotrypsin for agrin is further enhanced by exosite interactions [4,7]. However, short peptides only consisting of the amino acid sequence of the αor β-site are not cleaved by neurotrypsin, indicating that the specificity of neurotrypsin for agrin is further enhanced by exosite interactions [4,7].…”
Section: Introductionmentioning
confidence: 99%